2013
DOI: 10.1186/1476-4598-12-67
|View full text |Cite
|
Sign up to set email alerts
|

Id4 deficiency attenuates prostate development and promotes PIN-like lesions by regulating androgen receptor activity and expression of NKX3.1 and PTEN

Abstract: BackgroundInhibitor of differentiation 4 (Id4), a member of the helix-loop-helix family of transcriptional regulators has emerged as a tumor suppressor in prostate cancer. Id4 is expressed in the normal prostate where its expression is also regulated by androgens. In this study we investigated the effect of loss of Id4 (Id4-/-) on adult prostate morphology.MethodsHistological analysis was performed on prostates from 6-8 weeks old Id4-/-, Id4+/- and Id4+/+ mice. Expression of Id1, Sox9, Myc, androgen receptor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 72 publications
3
41
0
Order By: Relevance
“…In adult human tissues, ID4 expression is observed in brain, thyroid, testis and pancreas [21]. ID4 is also required for normal mammary [22] and prostate gland development [23]. …”
Section: The Role Of Id4 During Development and Differentiationmentioning
confidence: 99%
See 2 more Smart Citations
“…In adult human tissues, ID4 expression is observed in brain, thyroid, testis and pancreas [21]. ID4 is also required for normal mammary [22] and prostate gland development [23]. …”
Section: The Role Of Id4 During Development and Differentiationmentioning
confidence: 99%
“…ID4 is highly expressed in osteoblasts [24], adipocytes [25], prostate epithelial cells [23] neurons [26], testicular Sertoli cells [27] and during differentiation in glial cells [28] supporting its role as a pro-differentiation factor. ID4 is also expressed in germ cells at various stages of development: spermatogonial stem cells [29], spermatocytes, pachytene spermatocytes and spermatids [30].…”
Section: The Role Of Id4 During Development and Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, ID4 is expressed in hormonally regulated tissues including the breast, ovaries and prostate and is required for normal development (Shan et al 2003, Dong et al 2011, Sharma et al 2013, Best et al 2014, Junankar et al 2015. ID4 is stimulated by progesterone receptor (PR) activity through direct binding of ligand-activated PR to the ID4 promoter (Fernandez-Valdivia et al 2008).…”
Section: :9mentioning
confidence: 99%
“…Only 20% of mice survive on an Id4-null background, following a high proportion of embryonic and post-partum lethality resulting from severe brain and neuronal abnormalities (Bedford et al, 2005;Yun et al, 2004). In the male reproductive system, Id4 loss results in significantly reduced seminal vesicle size, prostatic intraepithelial neoplasia (PIN) lesions and sterility (Sharma et al, 2013), while a recent study in the mammary gland has shown that Id4 governs ductal elongation and branching via the Id4 target p38MAPK (Dong et al, 2011). In breast epithelial cells, Id4 negatively controls expression of the key tumor suppressor Brca1 (Beger et al, 2001) and also suppresses miR335, a positive regulator of Brca1 (Heyn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%